Predictors of residual tumor in breast-conserving therapy - Rath, Michèlle Geneviève; Uhlmann, Lorenz; Heil, Jörg; Domschke, Christoph; Roth, Zdravka; Sinn, Peter; Marmé, Frederik; Scharf, Alexander; Schneeweiss, Andreas; Kieser, Meinhard; Sohn, Christof; Rom, Joachim (Annals of surgical oncology, 2015)
Breast-conserving therapy is considered to be the standard treatment for early breast tumors (T1-T2). In up to 82 % of breast-conserving surgery, tumor cells were still found to be present at or near the cut edge of the surgical specimen after surgery. Thus, it is of clinical need to identify tumors at high probability for reexcision in the preoperative setting.